THE SYSTEM OF SPIRITUAL AND MORAL TECHNOLOGIES IN TRAINING MANAGERIAL PERSONNEL - Oripov Shukhratjon (Bright Mind Publishing, 2026)
This article analyzes the role and significance of spiritual and moral technologies in the training of managerial personnel. It highlights the potential of modern pedagogical and moral technologies in developing ethical culture, social responsibility, justice, and civic values among leaders. The study substantiates the effectiveness of a systemic and integrative approach in the professional training of managerial staff.
Keywords: Managerial personnel, spiritual and moral technologies, professional competence, educational system, social responsibility.